2015
DOI: 10.3390/nu7064978
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Toxicity of Sodium Selenite in the Treatment of Patients with Carcinoma in a Phase I Clinical Trial: The SECAR Study

Abstract: Background: Sodium selenite at high dose exerts antitumor effects and increases efficacy of cytostatic drugs in multiple preclinical malignancy models. We assessed the safety and efficacy of intravenous administered sodium selenite in cancer patients’ refractory to cytostatic drugs in a phase I trial. Patients received first line of chemotherapy following selenite treatment to investigate altered sensitivity to these drugs and preliminary assessment of any clinical benefits. Materials and Methods: Thirty-four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 24 publications
6
101
0
4
Order By: Relevance
“…For in vivo mouse xenograft studies 1.5 mg selenite/kg body weight and 20 mg carmustine/kg body weight were selected for use in combination. The dose of 1.5 mg of selenite/kg body weight in mouse translates to 4.44 mg/m 2 in humans and is less than the maximal tolerance dose of selenite shown in phase‐1 clinical trials (10.2 mg/m 2 ) . Similarly, the dose of 20 mg of carmustine/kg body weight in mouse translates to 59.9 mg/m 2 in humans, less than the dose used in phase‐1 clinical trials (450 mg/m 2 ) .…”
Section: Methodsmentioning
confidence: 96%
“…For in vivo mouse xenograft studies 1.5 mg selenite/kg body weight and 20 mg carmustine/kg body weight were selected for use in combination. The dose of 1.5 mg of selenite/kg body weight in mouse translates to 4.44 mg/m 2 in humans and is less than the maximal tolerance dose of selenite shown in phase‐1 clinical trials (10.2 mg/m 2 ) . Similarly, the dose of 20 mg of carmustine/kg body weight in mouse translates to 59.9 mg/m 2 in humans, less than the dose used in phase‐1 clinical trials (450 mg/m 2 ) .…”
Section: Methodsmentioning
confidence: 96%
“…Notably, high concentrations of sodium selenite, such as 10 g, might be associated with severe adverse events such as vomiting, nausea, severe headache, nail discoloration or brittleness, hair loss, or fatigue, whereas no adverse effects have yet been reported in any of the clinical studies that have been performed with Se . A recent intervention trial with patients with cancer has indicated that the total amounts of Se that can be tolerated without severe adverse effects are indeed in the mg range . Given these aspects about the right form of application and the clinical findings reported in the most recent meta‐analysis, the most adequate supplementation strategy is still unknown and may differ among clinical scenarios.…”
Section: The Role Of Se In Cardiac Surgerymentioning
confidence: 99%
“…This is a fact to take into account regarding clinical situations, since some of these inducer molecules could be provided during a S. maltophilia infection treatment. For instance, sodium selenite has been recently administered during a phase I clinical trial in terminal cancer patients (58) due to its cytotoxic effect on proliferating cancer cells. Since these patients are delicately vulnerable to infections caused by MDR Gram-negative bacteria, such as S. maltophilia (59), the dispensation of sodium selenite could lead to the overexpression of smeVWX and thus, transient resistance to its substrates.…”
Section: Discussionmentioning
confidence: 99%